Did inequality cause the U.S. financial crisis? - Till van Treeck (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2012)
In his widely discussed book "Fault Lines" (2010), Raghuram Rajan argues that many U.S. consumers have reacted to the decline in their relative permanent incomes since the early 1980s by reducing saving and increasing debt. This has temporarily kept private consumption and thus aggregate demand and employment high, despite stagnating incomes for many households. But it also contributed to the creation of a credit bubble, which eventually burst, and a large current account deficit in the United States. We place the Rajan hypothesis in the context of competing theories of consumption, and survey the empirical literature on the effects of inequality on household behaviour beyond the largely anecdotal evidence provided in Rajan (2010). We argue that the Rajan hypothesis, supported by the empirical evidence, calls for a renaissance of the relative income hypothesis of consumption.
urn:nbn:de:101:1-201209287434
Keywords: 330; Great Recession; income inequality; household dept; consumpion theory; Finanzkrise; Gesamtwirtschaftlicher Konsum; Einkommensverteilung; Schulden; Einkommenshypothese; USA